Linked Birth/Infant Death Data, 1987 Birth Cohort: (United States) ([Verlag nicht ermittelbar], 1994)
This data collection consists of two data files, which can be used to determine infant mortality rates. The first file provides linked records of live births and deaths of children born in the United States in 1987 (residents and nonresidents). This file is referred to as the "numerator" file. The second file consists of live births in the United States in 1987 and is referred to as the "denominator" file. Variables include year of birth, state and county of birth, characteristics of the infant (age, sex, race, birth weight, gestation), characteristics of the mother (origin, race, age, education, marital status, state of birth), characteristics of the father (origin, race, age, education), pregnancy items (prenatal care, live births), and medical data.